Assessment of JAVA code quality: Examining the efficacy of an automated tool as a teacher’s assistant - Margounakis, Dimitrios; Sofronas, Dimitrios; Rigou, Maria; Pachidis, Theodore (Συνέδρια της Ελληνικής Επιστημονικής Ένωσης Τεχνολογιών Πληροφορίας & Επικοινωνιών στην Εκπαίδευση, 2024)
Several contemporary software tools are available for measuring a range of object-oriented software quality metrics. In this study, we examine the efficacy of our automated tool, SQMetrics, which has been developed for educational purposes and can calculate the most popular metrics that have been proposed over time, giving special importance to object-oriented metrics. The tool is tested experimentally for its assistance in the evaluation of students’ Java programming assignments through statistical analysis. The results showed a positive correlation between the instructor’s rating and the overall quality index extracted from the software, indicating that the software tool could be a reliable assistant to instructor’s grading under certain circumstances.